Preparation method of self-sulfonated polyaromatic oxadiazole and base membrane
Through the manufacturing method of self-sulfonated polyarodiazole, the problems of high cost, large thickness limit and low transmittance of traditional proton exchange membrane materials are solved, and the proton exchange membrane with low cost, high transmittance and small thickness limit are realized, which improves the efficiency of the fuel cell and the durability and stability of the membrane.
Patent Information
- Application Number
- CN202411724679.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
Traditional proton exchange membrane materials such as Nafion have problems such as high cost, large thickness limits and low transmittance, which affects the efficiency and life of fuel cells.
By a production method of self-sulfonated polyarodiazole, dicarboxylic monomers and hydrazine salts are treated at a specific temperature and high temperature treatment is carried out to promote the formation of sulfonate, thereby improving proton mobility and transmittance.
A proton exchange membrane with low cost, high transmittance and small thickness limitations is achieved, which improves the efficiency of the fuel cell and the durability and stability of the membrane.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of proton exchange membranes, and in particular to a method for preparing self-sulfonated polyaromatic oxadiazole and a base membrane. Background Art
[0002] As one of the core components of fuel cells, the performance of proton exchange membrane directly affects the efficiency and life of the battery. Although traditional proton exchange membrane materials, such as Nafion, show good performance in fuel cells, they have some limitations and disadvantages:
[0003] Cost issue: The production cost of traditional proton exchange membrane materials such as Nafion is high, which limits its feasibility in large-scale commercial applications;
[0004] Membrane thickness limitation: The traditional solution casting method can usually only produce membranes with a thickness of no more than 50 microns. Although extrusion casting can produce thicker membranes, its permeability is low, which affects the performance of fuel cells;
[0005] Structural influence: Low permeability membrane materials have a certain impact on the structural design of fuel cells, which may lead to reduced battery efficiency;
[0006] Therefore, it is necessary to improve the above problems and realize a proton exchange membrane solution with better performance and lower cost. Summary of the invention
[0007] The present invention aims at the defects of the prior art such as high cost, large thickness limitation, low transmittance, etc., and provides a new method for preparing self-sulfonated polyaromatic oxadiazole and a base film.
[0008] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:
[0009] A method for preparing a self-sulfonated polyaromatic oxadiazole comprises the following steps: placing a dicarboxyl monomer in a 20wt% to 50wt% acidic solvent, maintaining the temperature at 75°C to 95°C for 1h to 2h, then adding a hydrazine salt in an equal molar amount to the dicarboxyl monomer, maintaining the temperature at 75°C to 95°C for 3h to 4h, then heating the temperature to 100°C to 120°C and maintaining the temperature for 1h to 2h, then heating the temperature to 140°C to 160°C and maintaining the temperature for 1h to 2h to obtain a slurry, and subjecting the slurry to coagulation bath molding, alkali washing, water washing, drying, and heat setting to obtain the polyaromatic oxadiazole.
[0010] By treating dicarboxyl monomers and hydrazine salts at a specific temperature, and subsequent high-temperature treatment, the generation of sulfonate groups can be effectively promoted, and these sulfonate groups provide new paths for the transmission and exchange of protons, thereby improving the proton mobility of the polyaromatic oxadiazole membrane, thereby improving the transmittance. The lone electron pair of the five-membered ring of polyaromatic oxadiazole itself provides a jumping transmission path for cations, and the introduction of sulfonate groups also provides a new path for the transmission and exchange of protons. Under the dual effects of lone electron pairs and sulfonate groups, even thick films have a high proton mobility, which reduces the thickness limit. By accurately controlling the reaction temperature and time, as well as subsequent coagulation bath molding, alkali washing, water washing, drying and heat setting steps, a polyaromatic oxadiazole membrane with a certain thickness and good mechanical properties can be prepared, which helps to improve the durability and stability of the membrane and reduce the thickness limit. By controlling the reaction conditions and post-treatment steps, the microstructure of the polyaromatic oxadiazole membrane can be optimized, defects can be reduced, and the uniformity and consistency of the membrane can be improved. Sulfonation in an acidic solvent, followed by high-temperature treatment, helps improve the chemical stability of the polyoxadiazole membrane, giving it a longer life in applications such as fuel cells. This manufacturing method may reduce production costs compared to traditional proton exchange membrane materials, making polyoxadiazole membranes more feasible for large-scale commercial applications.
[0011] The present invention realizes the manufacture of a low-cost self-sulfonated polyaromatic oxadiazole through the above design, with high transmittance and small thickness restriction.
[0012] Preferably, in the above-mentioned method for producing a self-sulfonated polyaromatic oxadiazole, the acidic solvent is fuming sulfuric acid, polyphosphoric acid or a mixture of the two, and the solid content of free SO3 in the fuming sulfuric acid is 20% to 50%.
[0013] Oleum contains a high concentration of free SO3, which enhances the activity of the sulfonation reaction and helps to effectively introduce sulfonic acid groups on the benzene ring of the dicarboxyl monomer and improve the sulfonation degree of polyaromatic oxadiazole. The introduction of sulfonic acid groups provides a pathway for proton hopping transmission for polyaromatic oxadiazole, thereby improving its proton conductivity as a proton exchange membrane. As an acidic solvent, a mixture of oleum and polyphosphoric acid can improve the chemical stability of polyaromatic oxadiazole membranes, giving them a longer service life in applications such as fuel cells. The enhancement of the sulfonation reaction helps to improve the mechanical properties of polyaromatic oxadiazole membranes, including strength and toughness, and improve the durability of the membrane. The strong acidity and dehydration of oleum can improve the efficiency of the sulfonation reaction, shorten the reaction time, and thus improve production efficiency. As an acidic solvent, polyphosphoric acid is weaker in acidity than nitric acid and sulfuric acid, and has no oxidizing ability, which helps to maintain the thermal stability of the material during the sulfonation process. Compared with traditional sulfonating agents, a mixture of oleum and polyphosphoric acid may have a lower cost, which helps to reduce the production cost of proton exchange membranes.
[0014] Preferably, in the above-mentioned method for producing a self-sulfonated polyoxadiazole, the dicarboxyl monomer is a mixture of one or more of 4,4'-diphenylether dicarboxylic acid, dimethyl terephthalate, dimethyl isophthalate, halogenated isophthalic acid, phosphorus-containing dicarboxyls, and sulfur-containing dicarboxyls.
[0015] The above-mentioned dicarboxyl monomers can undergo sulfonation reaction in a certain concentration of fuming sulfuric acid, and sulfonate groups are generated at specific positions of the benzene rings. The generation of sulfonate groups does not affect the reaction of dicarboxyl with hydrazine salts, so there will be more sulfonate groups on the final synthesized molecular chain. The presence of sulfonate groups can promote the migration and circulation of protons, ensuring the sulfonation degree and proton conductivity of polyaromatic oxadiazole. Phosphorus- and sulfur-containing dicarboxyl monomers can improve the chemical stability of polyaromatic oxadiazole membranes, making them have a longer service life in applications such as fuel cells. By using a mixture of multiple dicarboxyl monomers, the mechanical properties of polyaromatic oxadiazole membranes, including strength and toughness, can be optimized, and the durability of the membrane can be improved.
[0016] Preferably, in the above-mentioned method for producing a self-sulfonated polyarylene oxadiazole, the hydrazine salt is one of hydrazine sulfate and hydrazine hydrochloride or a mixture of both.
[0017] Both hydrazine sulfate and hydrazine hydrochloride have strong reducing properties. The addition of hydrazine salts can improve the efficiency of the polyoxadiazole synthesis reaction and promote the polymerization reaction of dicarboxyl monomers and hydrazine. The addition of hydrazine salts helps to improve the chemical stability and mechanical properties of polyoxadiazole membranes. Hydrazine salts can react with monomers to generate more stable polymer structures. The addition of hydrazine salts helps to improve the proton conductivity of polyoxadiazole membranes because hydrazine salts can provide additional proton hopping transmission pathways, thereby improving proton mobility.
[0018] Preferably, in the above-mentioned method for producing a self-sulfonated polyaromatic oxadiazole, when adding the hydrazine salt, a blending material is also added, and the blending material is a mixture of one or more of polytetrafluoroethylene, cellulose, carbon fiber, polyimide, graphene, and graphene oxide.
[0019] By blending, a polyoxadiazole membrane of a certain thickness can be prepared, the strength of the polyoxadiazole itself can be enhanced, structural defects can be reduced, and it can have stronger stability in fuel cells. The addition of blending materials such as polyimide and polytetrafluoroethylene can increase the maximum operating temperature and thermal stability of the proton exchange membrane. Blending materials such as carbon fiber can significantly improve the elastic modulus and wear resistance of the composite material and reduce the wear rate. Polytetrafluoroethylene has high corrosion resistance, self-lubricity and high temperature resistance, and its addition can improve the corrosion resistance of the membrane. The addition of cellulose and graphene can significantly improve the mechanical strength and toughness of the proton exchange membrane and improve its durability in practical applications. The addition of graphene and graphene oxide can increase the conductivity of the membrane and improve the efficiency and performance of the fuel cell.
[0020] Preferably, in the method for preparing a self-sulfonated polyarylene oxadiazole described above, after adding the hydrazine salt and the blending material, the temperature is maintained at 75°C to 95°C for 3h to 4h. If the added blending material includes polytetrafluoroethylene, the temperature is maintained at 90°C to 95°C for 3h to 4h. If the added blending material includes cellulose, the temperature is maintained at 75°C to 80°C for 3h to 4h. If the added blending material includes polytetrafluoroethylene and cellulose, the temperature is maintained at 75°C to 95°C for 3h to 4h.
[0021] By maintaining the mixture at a specific temperature for a certain period of time, the reaction between the blended material and the hydrazine salt can be enhanced, thereby improving the thermal stability of the final proton exchange membrane. The addition of the blended material and the maintenance time at a specific temperature help improve the mechanical properties of the membrane and increase its durability in practical applications.
[0022] Preferably, in the above-mentioned method for producing a self-sulfonated polyarylene oxadiazole, the solution used for the coagulation bath molding is a dilute sulfuric acid solution, the solid content of the dilute sulfuric acid solution is 1% to 35%, and the temperature of the dilute sulfuric acid solution is maintained at 0°C to 10°C.
[0023] Coagulation bath molding requires dilution of oleum in an acidic solvent, and a lower coagulation bath temperature is used to control the heat during the dilution process. Control of the coagulation bath temperature has a significant effect on the pore structure of the membrane. A lower coagulation bath temperature helps to form a pore structure and increase the porosity of the membrane, which may increase the permeability of the membrane. Coagulation bath molding at low temperatures can reduce the speed of phase separation caused by heat and help form a more uniform membrane structure. A lower coagulation bath temperature helps to improve the mechanical properties of the membrane. The membrane structure formed under low temperature conditions is denser, thereby improving the strength of the membrane.
[0024] Preferably, in the above-mentioned method for producing a self-sulfonated polyarylene oxadiazole, the solution used for the alkaline washing is one of lithium hydroxide, sodium hydroxide and potassium hydroxide.
[0025] Using lithium hydroxide, sodium hydroxide or potassium hydroxide for alkaline washing can effectively remove acidic substances and other impurities that may remain during the manufacturing process and improve the purity of the proton exchange membrane. Sodium hydroxide is selected based on cost, and lithium hydroxide is selected based on utility, but they cannot be mixed.
[0026] Preferably, in the above-mentioned method for producing a self-sulfonated polyaromatic oxadiazole, the drying is hot roller pressing drying, and the hot roller pressing pressure is 10 MPa to 20 MPa.
[0027] Hot roller drying can make the membrane material more dense and uniform through pressure at high temperature, reduce porosity, and improve the overall performance of the membrane. Hot roller drying can increase the mechanical strength and toughness of the membrane, making it more durable in subsequent use. Hot roller drying can smooth the membrane surface, reduce surface roughness, and help improve the flatness and appearance quality of the membrane.
[0028] Preferably, in the above-mentioned method for producing a self-sulfonated polyarylene oxadiazole, the heat setting temperature is above 280°C, the heat setting stretching is transverse stretching or simultaneous stretching in transverse and longitudinal directions, and the transverse tension is above 300N.
[0029] The mechanical strength of the film can be enhanced by heat setting at temperatures above 280°C. High-temperature heat setting helps optimize the microstructure of the film, making the polymer chains more ordered, thereby improving the uniformity and consistency of the film. Transverse stretching or simultaneous stretching in both the transverse and longitudinal directions improves the stability and durability of the film.
[0030] Preferably, a base film comprises polyaromatic oxadiazole manufactured by the manufacturing method described above.
[0031] Polyarylene oxadiazole can be used in polyarylene oxadiazole membranes. Polyarylene oxadiazole membranes can be used as base membranes to prepare polyarylene oxadiazole composite membranes or plates. They are mainly used in proton exchange membranes in the field of hydrogen fuel cells and proton exchange membranes in other fields. They can be used in the fuel cell industry and can also be used as base membranes for high thermal conductivity graphite and graphene membranes. After pyrolysis, carbon materials such as graphite can be synthesized for use in the heat dissipation field. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with specific embodiments, but they are not intended to limit the present invention:
[0033] Example 1
[0034] A method for preparing a self-sulfonated polyaromatic oxadiazole comprises the following steps: placing a dicarboxyl monomer in a 20wt% to 50wt% acidic solvent, maintaining the temperature at 75°C to 95°C for 1h to 2h, then adding a hydrazine salt in an equal molar amount to the dicarboxyl monomer, maintaining the temperature at 75°C to 95°C for 3h to 4h, then heating the temperature to 100°C to 120°C and maintaining the temperature for 1h to 2h, then heating the temperature to 140°C to 160°C and maintaining the temperature for 1h to 2h to obtain a slurry, and subjecting the slurry to coagulation bath molding, alkali washing, water washing, drying, and heat setting to obtain the polyaromatic oxadiazole.
[0035] Preferably, the acidic solvent is oleum, polyphosphoric acid or a mixture of the two, and the solid content of free SO3 in the oleum is 20% to 50%.
[0036] Preferably, the dicarboxyl monomer is a mixture of one or more of 4,4'-diphenylether dicarboxylic acid, dimethyl terephthalate, dimethyl isophthalate, halogenated isophthalic acid, phosphorus-containing dicarboxyls, and sulfur-containing dicarboxyls.
[0037] Preferably, the hydrazine salt is one of hydrazine sulfate and hydrazine hydrochloride or a mixture of both.
[0038] Preferably, when the hydrazine salt is added, a blending material is also added, wherein the blending material is a mixture of one or more of polytetrafluoroethylene, cellulose, carbon fiber, polyimide, graphene, and graphene oxide.
[0039] Preferably, after adding the hydrazine salt and the blending material, the temperature is maintained at 75°C to 95°C for 3h to 4h, if the added blending material includes polytetrafluoroethylene, the temperature is maintained at 90°C to 95°C for 3h to 4h, if the added blending material includes cellulose, the temperature is maintained at 75°C to 80°C for 3h to 4h, if the added blending material includes polytetrafluoroethylene and cellulose, the temperature is maintained at 75°C to 95°C for 3h to 4h.
[0040] Preferably, the solution used for the coagulation bath molding is a dilute sulfuric acid solution, the solid content of the dilute sulfuric acid solution is 1% to 35%, and the temperature of the dilute sulfuric acid solution is maintained at 0°C to 10°C.
[0041] Preferably, the solution used for the alkaline washing is one of lithium hydroxide, sodium hydroxide and potassium hydroxide.
[0042] Preferably, the drying is hot roller pressing drying, and the hot roller pressing pressure is 10MPa to 20MPa.
[0043] Preferably, the temperature of the heat setting is above 280° C., the stretching of the heat setting is transverse stretching or simultaneous stretching in transverse and longitudinal directions, and the transverse tensile force is above 300N.
[0044] Preferably, a base film comprises polyaromatic oxadiazole manufactured by the manufacturing method described above.
[0045] 20wt% to 50wt% of the acidic solvent may be 20wt%, 35wt%, 50wt%, and usually 50wt%.
[0046] Maintain the temperature at 75°C ~ 95°C for 1h ~ 2h. The temperature can be 75°C, 85°C, 95°C, usually 85°C. The holding time can be 1h, 1.5h, 2h, usually 1.5h.
[0047] Maintain the temperature at 75°C to 95°C for 3h to 4h. The temperature can be 75°C, 85°C, or 95°C, and 85°C is usually selected. The holding time can be 3h, 3.5h, or 4h, and 3.5h is usually selected.
[0048] Raise the temperature to 100℃~120℃ and keep it for 1h~2h. The temperature can be 100℃, 110℃, 120℃, usually 120℃. The keeping time can be 1h, 1.5h, 2h, usually 2h.
[0049] Raise the temperature to 140°C-160°C and maintain for 1h-2h. The temperature can be 140°C, 155°C, 160°C, usually 155°C. The holding time can be 1h, 1.5h, 2h, usually 2h.
[0050] The solid content of free SO3 in oleum can be 20%, 35%, or 50%, with 35% being usually selected.
[0051] Add hydrazine salt and blending materials. If the added blending material includes polytetrafluoroethylene, keep the temperature at 90℃~95℃ for 3h~4h. The temperature can be 90℃, 92.5℃, 95℃, usually 92.5℃, and the holding time can be 3h, 3.5h, 4h, usually 3.5h. If the added blending material includes cellulose, keep the temperature at 75℃~80℃ for 3h~4h. The temperature can be 75℃, 77.5℃, 80℃, usually 77.5℃, and the holding time can be 3h, 3.5h, 4h, usually 3.5h. If the added blending material includes polytetrafluoroethylene and cellulose, keep the temperature at 75℃~95℃ for 3h~4h. The temperature can be 75℃, 85℃, 95℃, usually 85℃, and the holding time can be 3h, 3.5h, 4h, usually 3.5h.
[0052] The temperature of the dilute sulfuric acid solution can be maintained at 0°C, 5°C, or 10°C, with 5°C being the most common.
[0053] The pressure of the hot roller pressing can be 10MPa, 15MPa, or 20MPa, and 15MPa is usually selected.
[0054] The heat setting temperature is above 280°C, may be 300°C, and usually does not exceed 450°C.
[0055] The tensile force in transverse stretching and transverse stretching in simultaneous transverse and longitudinal stretching is above 300N, and usually does not exceed 10000N.
[0056] Compared with the commonly used Nafion in the industry:
[0057] Cost: The cost of polyoxadiazole is only 10% of that of Nafion;
[0058] Ion exchange capacity: Nafion is 1.0 mmol / g to 2.0 mmol / g, polyaromatic oxadiazole is 1.0 mmol / g to 2.0 mmol / g;
[0059] Thickness range: Nafion is 25μm or 50μm, polyoxadiazole is more than 25μm;
[0060] Thermal stability: Nafion can withstand heat temperatures of 80°C to 120°C, and polyoxadiazole can withstand heat temperatures of more than 300°C.
[0061] In conclusion, the above is only a preferred embodiment of the present invention, and all equivalent changes and modifications made within the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for producing a self-sulfonated polyarylene oxadiazole, characterized in that: The following steps are involved: The dicarboxyl monomer is placed in a 20wt% to 50wt% acidic solvent, and the temperature is maintained at 75°C to 95°C for 1h to 2h, and then a hydrazine salt in an equal molar amount to the dicarboxyl monomer is added, and the temperature is maintained at 75°C to 95°C for 3h to 4h, and then the temperature is increased to 100°C to 120°C and maintained for 1h to 2h, and then the temperature is increased to 140°C to 160°C and maintained for 1h to 2h to obtain a slurry, and the slurry is subjected to coagulation bath molding, alkali washing, water washing, drying, and heat setting to obtain a polyaromatic oxadiazole.
2. The method for producing a self-sulfonated polyaromatic oxadiazole according to claim 1, characterized in that: The acidic solvent is one of fuming sulfuric acid and polyphosphoric acid or a mixture of the two, and the solid content of free SO3 in the fuming sulfuric acid is 20% to 50%.
3. The method for producing a self-sulfonated polyarylene oxadiazole according to claim 1, characterized in that: The dicarboxyl monomer is a mixture of one or more of 4,4'-diphenyl ether dicarboxylic acid, dimethyl terephthalate, dimethyl isophthalate, halogenated isophthalic acid, phosphorus-containing dicarboxyls, and sulfur-containing dicarboxyls.
4. The method for producing a self-sulfonated polyarylene oxadiazole according to claim 1, characterized in that: The hydrazine salt is one of hydrazine sulfate and hydrazine hydrochloride or a mixture of both.
5. The method for producing a self-sulfonated polyaromatic oxadiazole according to claim 1, characterized in that: When the hydrazine salt is added, a blending material is also added, wherein the blending material is a mixture of one or more of polytetrafluoroethylene, cellulose, carbon fiber, polyimide, graphene, and graphene oxide.
6. The method for producing a self-sulfonated polyarylene oxadiazole according to claim 5, characterized in that: After adding the hydrazine salt and the blending material, the temperature is maintained at 75°C to 95°C for 3h to 4h. If the added blending material includes polytetrafluoroethylene, the temperature is maintained at 90°C to 95°C for 3h to 4h. If the added blending material includes cellulose, the temperature is maintained at 75°C to 80°C for 3h to 4h. If the added blending material includes polytetrafluoroethylene and cellulose, the temperature is maintained at 75°C to 95°C for 3h to 4h.
7. The method for producing a self-sulfonated polyarylene oxadiazole according to claim 1, characterized in that: The solution used for the coagulation bath molding is a dilute sulfuric acid solution, the solid content of the dilute sulfuric acid solution is 1% to 35%, and the temperature of the dilute sulfuric acid solution is maintained at 0°C to 10°C.
8. The method for producing a self-sulfonated polyaromatic oxadiazole according to claim 1, characterized in that: The solution used for the alkaline washing is one of lithium hydroxide, sodium hydroxide and potassium hydroxide.
9. The method for producing a self-sulfonated polyaromatic oxadiazole according to claim 1, characterized in that: The drying is hot roller pressing drying, and the pressure of the hot roller pressing is 10MPa to 20MPa.
10. The method for producing a self-sulfonated polyaromatic oxadiazole according to claim 1, characterized in that: The temperature of the heat setting is above 280° C., the stretching of the heat setting is transverse stretching or synchronous stretching in transverse and longitudinal directions, and the transverse tensile force is above 300N.
11. A basement membrane, characterized in that: The present invention comprises a polyarylene oxadiazole produced by the production method according to any one of claims 1 to 10.